The art of defiance : graffiti, politics, and the reimagined city in Philadelphia - Mitman, Tyson (Intellect, 2018)
The Art of Defiance is an ethnographic portrait of how graffiti writers see their city and, in turn, how their city sees them. It explores how becoming a graffiti writer helps disenfranchised urban citizens negotiate their cultural identities, build their social capital and gain a voice within an urban environment that would prefer they remain quiet, passive and anonymous. In order to both demystify and complicate our understanding of the practice of graffiti writing, this book pushes past the narrative that links the origins of graffiti to criminal gangs and instead offers a detailed portra.